The clinical course and prognosis factors of stomach cancer patients with metastases in the ovaries - S. N. Tadzhibov; S. B. Polikarpova; T. M. Kochoyan; A. S. Ozherel’ev; R. A. Kerimov; A. I. Berishvili (Опухоли женской репродуктивной системы, 2017)
We analyzed the data of 53 patients with metastatic gastric cancer in ovaries treated in the N.N. Blokhin Russian Cancer Research Center in 2009–2014. These patients are the main group. The control group consisted of 55 patients stage III–IV locally advanced gastric cancer without metastases in the ovaries treated with surgical and combined treatment in the period from 2009 to 2014. The main group and control group were matched by major demographic and clinical characteristics. It was found that gastric cancer patients stage III–IV are prognostically unfavorable group. More than half of patients (51 %) with disseminated cancer of the stomach simultaneously diagnosed metastatic ovarian failure. When studying the remote indicators, it is evident that the presence of metastases in the ovaries is significant unfavorable prognostic factor of 2 years overall survival of postmenopausal patients over 50 years old who received only surgical treatment. However, carrying out combined treatment of patients with metastases to the ovary, without significant impairment in the first year of observation, significantly increases the 3–5-year survival (68 %).